Application of gene chip technology in the diagnostic and drug resistance detection of Helicobacter pylori in children. Issue 8 (5th February 2020) - Yin, Guofeng; Bie, Shuxian; Gu, Hongdan; Shu, Xiaoli; Zheng, Wei; Peng, Kerong; Zhao, Hong; Li, Fubang; Chen, Bo; Botchway, Benson O A; Fang, Marong; Jiang, Mizu
Abstract: Background and Aims: Helicobacter pylori (HP) culture for diagnosing HP infection is time‐consuming and technologically complex. This study evaluated the clinical significance of gastric mucosal gene chip technology in the rapid diagnosis of HP infection and detection of drug resistance in children. Methods: Patients (between the age of 2.5 and 16.0 years old) manifesting gastrointestinal symptoms were enrolled in this study. HP culture of gastric mucosa and drug sensitivity test were performed. A gene chip of gastric mucosa was used to detect the presence of HP infection, some single nucleotide polymorphisms in HP drug resistance genes, or associated gene mutation. DNA sequencing was investigated and compared with the gene chip test results. Results: Out of 267 cases, HP culture was positive in 169 cases and negative in 98 cases. HP detection by the gene chip method was positive in 208 cases and negative in 59 cases. The sensitivity, specificity, and accuracy of the gene chip technology for diagnosing HP infection were 96.1, 85.0, and 93.6%, respectively. HP resistance gene locus using the gene chip showed the main mutation locus of clarithromycin to be 2143A/G, levofloxacin at locus GyrA 91 and GyrA 87, and amoxicillin at PBP1 556ser. Concordance rates between gene chip and DNA sequencing for VacA‐S/M, 16S rRNA, 23S rRNA, and GyrA were greater than 95%, and that of PBP1 was greater than 82%. Conclusion: Gastric mucosal gene chip technology can be used for rapid diagnosis and drug resistance detection of HP infection in children.